2014
DOI: 10.1177/0886260514555130
|View full text |Cite
|
Sign up to set email alerts
|

A Gender Comparison of Motivations for Physical Dating Violence Among College Students

Abstract: There are limited empirical investigations that directly compare men and women’s motivations, or reasons, for perpetrating physical dating violence (DV). In an attempt to further understand whether men and women have similar or different motives for physical DV, the purpose of the current study was to conduct a gender comparison motives in a sample of male (n = 163) and female (n = 319) college students. Motivations for physical DV were classified according to seven broad categories proposed by Langhinrichsen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 36 publications
(106 reference statements)
2
14
0
1
Order By: Relevance
“…Otro hallazgo digno de discusión es que hubo paridad entre los valores de violencia cometida por el grupo femenino y el grupo masculino. Previos estudios informaron sobre la bilateralidad de las agresiones en los noviazgos juveniles (Chan et al, 2008;Malik et al, 1997;Straus & Ramirez, 2007;Taylor & Mumford, 2016) e, incluso, sobre mayores valores en el grupo femenino (Arbach-Lucioni et al, 2015;Elmquist et al, 2016). Si bien en este estudio no se exploraron los subtipos determinados por la unidireccionalidad agresiva -sólo desde el varón a la mujer o sólo desde la mujer al varón-y por la bidireccionalidad (Straus & Gozjolko, 2014), los hallazgos están en línea con el planteo de la predominante reciprocidad de la violencia en las parejas de los jóvenes.…”
Section: Discussionunclassified
“…Otro hallazgo digno de discusión es que hubo paridad entre los valores de violencia cometida por el grupo femenino y el grupo masculino. Previos estudios informaron sobre la bilateralidad de las agresiones en los noviazgos juveniles (Chan et al, 2008;Malik et al, 1997;Straus & Ramirez, 2007;Taylor & Mumford, 2016) e, incluso, sobre mayores valores en el grupo femenino (Arbach-Lucioni et al, 2015;Elmquist et al, 2016). Si bien en este estudio no se exploraron los subtipos determinados por la unidireccionalidad agresiva -sólo desde el varón a la mujer o sólo desde la mujer al varón-y por la bidireccionalidad (Straus & Gozjolko, 2014), los hallazgos están en línea con el planteo de la predominante reciprocidad de la violencia en las parejas de los jóvenes.…”
Section: Discussionunclassified
“…Similarly, a review of 14 studies that examined dating violence victimization among female students found that the rate ranged from 11.7% to 39% (Williams, Ghandour, & Kub, 2008). Many scholars have pointed out that there is a long-lasting effect of psychological stress on victims well into their adulthood (Elmquist et al, 2016; Shorey, Brasfield, Febres, & Stuart, 2011).…”
mentioning
confidence: 99%
“…Research has shown that physically aggressive couples are more likely than nonviolent couples to respond to conflicts with hostile communication, including blaming, threatening, name-calling, and criticizing (Cornelius et al, 2010; Feldman & Ridley, 2000; Robertson & Murachver, 2007) and that communication difficulties motivate perpetration of IPV (Langhinrichsen-Rohling et al, 2012). A recent study that compared men and women’s motivations, or reasons, for perpetrating physical dating violence among college students, found that communication difficulties and self-defense were among the most frequently endorsed motive categories for both male- and female-perpetrated dating violence (Elmquist et al, 2016).…”
Section: The Moderating Role Of Communicationmentioning
confidence: 99%